1997
DOI: 10.1039/a608063d
|View full text |Cite
|
Sign up to set email alerts
|

Pb2+ and Cd2+ selective chemically modified field effect transistors based on thioamide functionalized 1,3-alternate calix[4]arenes

Abstract: Novel calix[4]arenes fixed in the 1,3-alternate conformation and functionalized with thioamide groups have been synthesized and their selectivities for Pb 2ϩ and Cd 2ϩ ions in chemically modified field effect transistors (CHEMFETs) have been evaluated. The 25,27-bis(dimethylaminothiocarbonylmethoxy)-26,28-dipropoxycalix[4]arene 3 in the 1,3-alternate conformation is more selective for Pb 2ϩ than the analogous cone conformer. The 1,3-alternate calix[4]arene 8 having, in the 25-and 27-positions, two pairs of vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The dialkylated intermediate is conformationally labile and there is evidence that metal ion template effects are important in determining whether or not the final product has the 1,3-alternate conformation [31][32][33][34][35][36][37]. The dialkylated intermediate is conformationally labile and there is evidence that metal ion template effects are important in determining whether or not the final product has the 1,3-alternate conformation [31][32][33][34][35][36][37].…”
Section: Type (B) -Open Cavities Rendered Inequi-valent By Different mentioning
confidence: 99%
“…The dialkylated intermediate is conformationally labile and there is evidence that metal ion template effects are important in determining whether or not the final product has the 1,3-alternate conformation [31][32][33][34][35][36][37]. The dialkylated intermediate is conformationally labile and there is evidence that metal ion template effects are important in determining whether or not the final product has the 1,3-alternate conformation [31][32][33][34][35][36][37].…”
Section: Type (B) -Open Cavities Rendered Inequi-valent By Different mentioning
confidence: 99%
“…A redox-active voltametric sensor based on a self-assembled monolayer of calix Reinhoudt et al 34 from an aqueous solution into organic layer with (20) has been described., 35a Chawla et al 67 have also reported the synthesis of calix [n]arenes (21a n=4, 21b n=8) with imidazole moieties directly atached to the upper rims. These heterocyclic calix [n]arenes have been shown to be highly selective extractants (>98%) for Ag + ions.…”
Section: Calixarene-based Receptors For Alkali and Alkaline Earth Metmentioning
confidence: 99%
“…The 25,27-bis(dimethylaminothiocarbonylmethoxy)-26,28-dipropoxycalix[4]arene 3 in the 1,3-alternate conformation was reported to be more selective for Pb 2+ than the analogous cone conformer. The 1,3-alternate calix[4]arene 8 having, in the 25- and 27-positions, two pairs of vicinal thioamide moieties at the same face of the molecule, had the highest selectivities for Cd 2+ [40]. In the same year, A. Ceresa, E. Bakker et al, used optimized ion-selective membranes based on the lead-selective ionophore 4-tert-butylcalix[4]arenetetrakis(thioacetic acid dimethylamide) [41].…”
Section: Application Of the Concept Of Supramolecular Chemistry In Thmentioning
confidence: 99%